Implementação de um gerador síncrono virtual e desenvolvimento de uma estratégia de sintonia para seu sistema de excitação e governador de velocidade - Souza, Sabrina de Angeli (2017)
The diffusing utilization of distributed generation units has changed the traditional structure dominated by synchronous machines and centralized power plants. Hence, as these sources have small rotating mass and are poorly damped, the VSG is a solution to improve power grid transient stability. The Virtual Synchronous Generator (VSG) consist in a control strategy to make a converter interface between a Distributed Generation unit and the grid operate as a Synchronous Machine. This Master’s thesis is focused on a VSG implementation and its control mechanism, including a methodology for controller tuning and stability improvement by means of the system eigenvalues location with respect to the controllers parameters. Models for all VSG elements are detailed in order to exhibit the relation of the voltage and speed controllers with system parameters. Finally, the validity and accuracy of the presented VSG are obtained comparing results from time-domain simulation of a VSG with an equivalent synchronous machine during some disturbance events.